Hubungan Faktor Kecepatan Door-To-ECG terhadap Keterlambatan Waktu Terapi Fibrinolitik pada Pasien ST-Elevation Myocardial Infarction (STEMI) di RSUD Prof.R.D. Kandou Manado - Johanis Kerangan; M. Rasjad Indra; Tony Suharsono (STIKes Patria Husada Blitar, 2015)
Reperfusion therapy is the main strategy in the treatment of patients with STEMI and when the reperfusion time faster, closely linked to the decrease rate of mortality. One of the deciding factors in intrahospital care system is the the speed of door-to-ECG are measured when the patient arrives at the emergency unit until being recorded ECG examination and the results can be interpreted by health personnel. This study aimed to analyze the correlation between the speed of door-to-ECG with the delay time of fibrinolytic therapy at the Emergency Department of Prof. R.D. Kandou general hospital in Manado.The method of this study was Prospective Cohort with analytic observational design. Sampling technique was consecutive sampling with 22 participant on June-July 2015 on emergency department of Prof. R.D. Kandou general hospital in Manado. Observation sheet was used as instrument. Bivariate analysis showed that there was a significant correlation between the speed of door-to-ECG with fibrinolitic therapy delay ( p value = 0.028) With rate of speed door-to-ECG is 28,59 minutes. The longer time door-to-ECG cause the longer fibrinolytic therapy that cause increasing mortality rate of STEMI patient.